Retinal nerve fiber layer defect patterns in primary angle-closure and open-angle glaucoma: A comparison using optical coherence tomography - Anita Manassakorn (2018)
Purpose: To compare the patterns of retinal nerve fiber layer (RNFL) thickness loss in primary angle-closure glaucoma (PACG) and primary open-angle glaucoma (POAG) using optical coherence tomography (OCT). Methods: Forty-three participants with PACG and 60 with POAG underwent fast RNFL thickness measurement by OCT. Eyes were classified according to the visual field mean deviation (VF-MD) into mild (>-8 dB), moderate (-8 dB to >-16 dB), and advanced (≤-16 dB) glaucoma subgroups. The raw RNFL thickness data were compared with data from the Thai normative database. Results: Mean (SD) age was 67.0 (9.6) and 64.1 (11.6) years in the PACG and POAG groups, respectively (P = 0.19). In the mild subgroups, a focal RNFL thickness loss was found in the inferior area in the POAG group, but not in the PACG group. The RNFL defect involved sectors 1, 6, and 7 in the moderately advanced disease subgroups of both PACG and POAG and extended through almost all sectors in the advanced disease subgroups. The deepest RNFL defect, -17.25 μm, was found in sector 6 of the mild POAG subgroup, compared with -8.78 μm in the PACG group (P = 0.04). The number of affected points in each sector in the mild subgroups was greater in the POAG group than in the PACG group. Conclusion: Participants with mild POAG had deeper and more localized RNFL defects than did participants with PACG. The pattern was similar in participants with moderate or advanced disease. © 2011 Japanese Ophthalmological Society (JOS).